Criminal responsibility of mining companies management board regarding offenses against the environment - Calderón Valverde, Leonardo Fernando (2016)
The purpose of this work is to establish, develop andunderstandthegeneralandspecificguidelines that serve as a legal platform to determine when a governing body, whatever legal representative is, usually the General Manager, and/or director, shareholder or partner, of a mining company, that may be held criminally responsible for the commission of a crime against the environment, under the assumption of an act of omission, that is, a title of omission by the breach of the duty of the guarantor (duty organizational), developing the special characteristics of the transfer of the institution of the act of omission in the business sector, ending our analysis to establish at what point this crime against the environment is attributable to the directors by intent or negligence.This by virtue of the fact that the responsible for administering justice, whether Public Ministry and Judiciary, when performing the legal qualification of the facts under investigat